Data Envelopment Analysis to Measure Efficiency of Hotels in Malaysia. - Foo, Lee Yen; Othman, Mohhidin (SEGi University College, 2011)
Performance evaluation has become an important improvement tool for hotels to be sustainable in today’s highly competitive environment. Although the evaluation of hotel efficiency has been approached from various perspectives, difficulties were encountered when multiple inputs and outputs relative to a hotel’s performance needed to be considered. The purpose of this paper is to examine Malaysian hotel efficiency by adopting an approach using a framework of non-parametric programming – Data Envelopment Analysis (DEA). DEA is very useful for application in a multiple inputs and outputs settings where it combines them objectively into an overall measure of organisational efficiency called the Malmquist’s Total Factor Productivity (TFP) index. It is concluded that DEA can be used to measure the efficiency of Malaysian hotels.